2006
DOI: 10.1016/j.jvs.2005.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical properties of ruptured versus electively repaired abdominal aortic aneurysm wall tissue

Abstract: Our data suggest that AAA rupture is associated with aortic wall weakening, but not with wall stiffening. A widely accepted indicator for risk of aneurysm rupture is the maximum transverse diameter. Our results suggest that AAA wall strength, in large aneurysms, is not related to the maximum transverse diameter. Rather, wall thickness or stiffness may be a better predictor of rupture for large AAAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
195
1
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(218 citation statements)
references
References 29 publications
9
195
1
13
Order By: Relevance
“…16,52 Di Martino et al have shown that the presence of ILT can significantly reduce wall stresses. [12][13][14][15] Fluid-structure interaction (FSI) simulations, in which a fully coupled dynamic interaction between the AAA hemodynamics and wall deformations is modeled, were conducted by our group and others to simulate the biomechanical behavior of the AAA wall. 3,14,18,36,48,60 Most previous FSI studies were based on isotropic material models that exclude the directional response of abdominal aortic tissue to stresses.…”
Section: Computational Simulations and Fluid-structure Interaction Momentioning
confidence: 99%
“…16,52 Di Martino et al have shown that the presence of ILT can significantly reduce wall stresses. [12][13][14][15] Fluid-structure interaction (FSI) simulations, in which a fully coupled dynamic interaction between the AAA hemodynamics and wall deformations is modeled, were conducted by our group and others to simulate the biomechanical behavior of the AAA wall. 3,14,18,36,48,60 Most previous FSI studies were based on isotropic material models that exclude the directional response of abdominal aortic tissue to stresses.…”
Section: Computational Simulations and Fluid-structure Interaction Momentioning
confidence: 99%
“…In computational simulations, vessel stress is calculated as a function of the vessel diameter [7,34], wall thickness [36,37], asymmetry [14,18,34,36], tortuosity [21], material property [17,24,29,38], calcification [15,22], intraluminal thrombus (ILT) [5,15,16,33], and blood flow [4, 9, 13, 14, 17, 20, 25, 26, 28-30, 32, 35-41]. Blood vessel strength is measured by ex vivo studies [11,12,23,31,44] or estimated by effective features such as ILT existence, sex, and genetic vulnerability [10]. Medical treatment techniques of aneurysms, mainly stent applications, are also investigated [35,40].…”
mentioning
confidence: 99%
“…In addition, Di Martino et al [51] suggested a weak (but significant) negative correlation (R ¼ À0.42 and P ¼ 0.012) between the AAA wall thickness and its tensile strength. Using their patients' data, we regenerated the trend line estimating the linear relation between the AAA wall thickness (h in mm) and the AAA wall tensile strength (r u in kPa) such that r u ¼ À170:43h þ 1224:7.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the inclusion of bending stiffness in our analysis intensifies the effects of spine contact on the morphology, wall stress distribution, and PWS, beyond what we observed in this study. Accurate measures of wall strength are yet to be considered in our analysis for a reliable assessment of rupture [50,51,57,58]. Our simulation cases represent hypothetical models of AAAs initiated by artificial elastin degradation in a healthy aorta instead of the real elastin loss in a patient's AAA wall.…”
Section: Discussionmentioning
confidence: 99%